2010
DOI: 10.1136/emj.2009.087288
|View full text |Cite
|
Sign up to set email alerts
|

Weight estimation in paediatrics: a comparison of the APLS formula and the formula 'Weight=3(age)+7'

Abstract: Weight estimation is of paramount importance in paediatric resuscitation. This study shows that the current estimation formula provides a significant underestimate of children's weights. When used to calculate drug and fluid dosages, this may lead to the under-resuscitation of a critically ill child. The formula 'Weight=3(age)+7' can be used over a larger age range (from 1 year to puberty) and allows a safe and more accurate estimate of the weight of children today.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 15 publications
5
55
1
2
Order By: Relevance
“…Weight estimation is used in emergency settings when trauma or pain prevent weighing of the child and active resuscitation is required. The formula given in the Advanced Pediatric Life Support course, which is taken throughout Europe, South Africa, Australia, and New Zealand, is weight (in kg) 5 (3 · age [in years]) 17, and we recommend that technologists become familiar with this formula (21). We also recommend that pediatric doses be calculated according to the European Association of Nuclear Medicine dosage card (22) or the Society of Nuclear Medicine and Molecular Imaging procedure standard (23).…”
Section: Discussionmentioning
confidence: 99%
“…Weight estimation is used in emergency settings when trauma or pain prevent weighing of the child and active resuscitation is required. The formula given in the Advanced Pediatric Life Support course, which is taken throughout Europe, South Africa, Australia, and New Zealand, is weight (in kg) 5 (3 · age [in years]) 17, and we recommend that technologists become familiar with this formula (21). We also recommend that pediatric doses be calculated according to the European Association of Nuclear Medicine dosage card (22) or the Society of Nuclear Medicine and Molecular Imaging procedure standard (23).…”
Section: Discussionmentioning
confidence: 99%
“…Glucose administration with 2.5% or 5% dextrose based saline solution at fluid maintenance rate : To compare EGP, as described by our regression model, with exogenous glucose supplementation using either a 2.5% or 5% dextrose-based saline solution infused at an age-specific fluid maintenance rate, we first calculated estimated body weight from age 1 to 18 years using the Luscombe weight formula29: …”
Section: Methodsmentioning
confidence: 99%
“…Whereas the study authors concluded that the new formula could be used safely in a UK population from 1 year to puberty,2 APLS limits its use to 6–12 years. We have not been able to find a clear rationale for this approach from a literature search.…”
mentioning
confidence: 92%
“…We understand that the introduction of the ‘Luscombe’ formula (3×age in years +7) into APLS was based on a retrospective study which showed that the ‘old’ APLS formulae underestimated children's weights 2. Whereas the study authors concluded that the new formula could be used safely in a UK population from 1 year to puberty,2 APLS limits its use to 6–12 years.…”
mentioning
confidence: 99%